The Effect of Innovative Behavior, Knowledge Sharing, and Engagement on Student Academic Achievement throught Knowledge Managemen - Saputri, Risma Nata; Hestri, Zulfa; Prameswari, Tiara Indri; Sembiring, Dian Arisandy Eka Putra; Yusuf, Muhammad; Wijaya, Hansein Arif; Aprillitzavivayarti, Aprillitzavivayarti (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2025)
This study aims to analyze the relationship between knowledge management, knowledge sharing, innovative behavior and student’s academic achievement using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. From the result of the analysis, all constructs of the research model have good validity and reliability, and the values of the loading factors, composite stability (CR), and average variance extracted (AVE) are expected to meet the criteria. The data normality test shows that the data distribution is mostly in accordance with normal standards, although there are small deviations that do not significantly affect the results of the analysis. The main result show that knowledge management has a positive effect the results of the analysis. The main results show that knowledge management has a positive effect on students’ innovative behavior and knowledge sharing acts as a moderator that strengthens the relationsip. In addition, innovative behavior has been shown to have a positive impact on students’ academic achievement, with more innovative students tending to have better academic achievement. These results highlight the importance of developing a culture that supports knowledge sharing and innovative behavior in educational institutions to improve academic achievement. Educational institutions are expected to create an environment that supports student collaboration, innovation, and creativity through activities such as group discussions, seminars, and joint projects. Keywords: Innovative Behavior, Knowledge Sharing, Student Engagement, Academic Achievement, Knowledge Management